Asean Integration In Improving Indonesian Women Education: A Literature Review - Rostiena Pasciana; Ieke Sartika Iriany (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2018)
The Association of Southeast Asian Nations (ASEAN) is an organization of countries in Southeast Asia established in Bangkok, Thailand, on August 8, 1967 under the Bangkok Declaration by Indonesia, Malaysia, Philippines, Singapore, and Thailand. For more th an five decades ASEAN has experienced many positive and significant developments towards a more integrative and forward - looking stage with the establishment of an ASEAN Community by 2015. The ASEAN Community not only affects the economic sector, but also other sectors, including